E GOVERNANCE AND RURAL DEVELOPMENTAN EMPIRICAL STUDY (International Journal of Food and Nutritional Sciences, 2019)
In recent years, India has witnessed a rapid transformation in its governance landscape throughthe adoption of Electronic Governance (E-Governance) initiatives. This abstract provides aglimpse into the dynamic evolution of E-Governance in India, highlighting key trends,challenges, and the overarching impact on citizens and administrative processes.